Peningkatan Loyalitas Nasabah Koperasi Sunan Drajat Banjarwati Paciran Lamongan Jawa Timur melalui Prinsip-Prinsip dan Penerapan Nilai-Nilai Islami - Siswadi Siswadi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
The Sunan Drajat Banjarwati Cooperative Paciran Lamongan is one of the growing financial services businesses that requires efforts to develop its business, one of its efforts is through customer loyalty in order to gain the trust of customers, with loyal customers by participating in advancing the Sunan Drajat Cooperative Banjarwati Paciran Lamongan. The formulation of the problem in this scientific paper is how the application of Islamic principles and values ​​in the Sunan Drajat Banjarwati Paciran Lamongan Cooperative in increasing customer loyalty and how the Sunan Drajat Banjarwati Paciran Lamongan Cooperative strategy in increasing customer loyalty. This research is a qualitative research that uses empirical methods. Qualitative research is research that describes a problem by not using quantitative, even if there are numbers, it is used as supporting data to complete. While the empirical method is research that aims to reveal the reality in the field by taking data based on the experience of respondents, where the law is seen as a fact because the law will interact with other social institutions. The purpose of analyzing these two things is to make a description of one object according to the facts so that the Sunan Drajat Banjarwati Paciran Lamongan Cooperative can get loyal customers in accordance with Islamic values. And the instruments of this research are interviews, observations, literature studies and questionnaires.